A New Configuration of A High Output Voltage 2.45 GHz Rectifier For Wireless Power Transmission Applications - A. Taybi; A. Tajmouati; J. Zbitou; A. Errkik; M. Latrach; L. El Abdellaoui (Universitas Ahmad Dahlan, 2018)
This work deals with the design, simulation, fabrication and experimentation of a novel 2.45 GHz rectifier for wireless power transmission applications. We have designed a voltage multiplier topology rectifier including 5 Schottky diodes known by their low threshold. This rectifier could perform a wireless power supply for many cases where the use of batteries or wires is impossible due to many limitations. The circuit was analyzed and optimized with the Harmonic Balance method provided by the Advanced Design System (ADS). Good performances are observed through the simulated results and confirmed by the fabrication tests in terms of RF-DC conversion efficiency, DC output voltage level and matching input impedance.